Usherin defects lead to early-onset retinal dysfunction in zebrafish. (August 2018) - Dona, Margo; Slijkerman, Ralph; Lerner, Kimberly; Broekman, Sanne; Wegner, Jeremy; Howat, Taylor; Peters, Theo; Hetterschijt, Lisette; Boon, Nanda; de Vrieze, Erik; Sorusch, Nasrin; Wolfrum, Uwe; et al.
Abstract: Mutations in USH2A are the most frequent cause of Usher syndrome and autosomal recessive nonsyndromic retinitis pigmentosa. To unravel the pathogenic mechanisms underlying USH2A -associated retinal degeneration and to evaluate future therapeutic strategies that could potentially halt the progression of this devastating disorder, an animal model is needed. The available Ush2a knock-out mouse model does not mimic the human phenotype, because it presents with only a mild and late-onset retinal degeneration. Using CRISPR/Cas9-technology, we introduced protein-truncating germline lesions into the zebrafish ush2a gene ( ush2a rmc1 : c.2337_2342delinsAC; p.Cys780GlnfsTer32 and ush2a b1245 : c.15520_15523delinsTG; p.Ala5174fsTer). Homozygous mutants were viable and displayed no obvious morphological or developmental defects. Immunohistochemical analyses with antibodies recognizing the N- or C-terminal region of the ush2a -encoded protein, usherin, demonstrated complete absence of usherin in photoreceptors of ush2a rmc1, but presence of the ectodomain of usherin at the periciliary membrane of ush2a b1245 -derived photoreceptors. Furthermore, defects of usherin led to a reduction in localization of USH2 complex members, whirlin and Adgrv1, at the photoreceptor periciliary membrane of both mutants. Significantly elevated levels of apoptotic photoreceptors could be observed in both mutants when kept under constant bright illumination for three days. Electroretinogram (ERG) recordings revealed a significant and similar decrease in both a- and b-wave amplitudes in ush2a rmc1 as well as ush2a b1245 larvae as compared to strain- and age-matched wild-type larvae. In conclusion, this study shows that mutant ush2a zebrafish models present with early-onset retinal dysfunction that is exacerbated by light exposure. These models provide a better understanding of the pathophysiology underlying USH2A -associated RP and a unique opportunity to evaluate future therapeutic strategies. Highlights: Ush2a zebrafish models present with early-onset retinal dysfunction. Retinal dysfunction is observed mainly in the absence of photoreceptor degeneration. Exposure to constant bright illumination induces photoreceptor apoptosis. Whrna and Whrnb have high binding-affinities for usherin and Adgrv1, respectively. The intracellular region of usherin has a critical role in retinal function.